1996
DOI: 10.1007/bf00142865
|View full text |Cite
|
Sign up to set email alerts
|

The Imperata grasslands of tropical Asia: area, distribution, and typology

Abstract: The rehabilitation or intensified use of lmperata grasslands will require a much better understanding of their area, distribution, and characteristics. We generated estimates of the area of Imperata grasslands in tropical Asia, and suggested a typology of Imperata grasslands that may be useful to define the pathways toward appropriate land use intensification. We conclude that the area of lmperata grasslands in Asia is about 35 million ha. This is about 4% of the total land area. The countries with the largest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(75 citation statements)
references
References 6 publications
(5 reference statements)
1
67
0
5
Order By: Relevance
“…Percent sand was higher in soils from the CDS than those from the SGS rvhile % silt and o/o clay followed the opposite trend. These results agree with previous research that has shown that speargrass occurs on soils with a lvide range of soil properties (Garrity et al, 1997;Santoso et al, 1991: Chikoye et al, 1999. In soils with inherent low soil fertility such as those encountered in this study, poor crop growth facilitates the growth and dominance of speargrass (Santoso et al, 1991).…”
Section: Eristing Weed Tnanagement Practicessupporting
confidence: 93%
See 1 more Smart Citation
“…Percent sand was higher in soils from the CDS than those from the SGS rvhile % silt and o/o clay followed the opposite trend. These results agree with previous research that has shown that speargrass occurs on soils with a lvide range of soil properties (Garrity et al, 1997;Santoso et al, 1991: Chikoye et al, 1999. In soils with inherent low soil fertility such as those encountered in this study, poor crop growth facilitates the growth and dominance of speargrass (Santoso et al, 1991).…”
Section: Eristing Weed Tnanagement Practicessupporting
confidence: 93%
“…Spcargrass llntperata cylinclrica (L.) Raueschel] is one of the most dominant, competiti.re, and difficult weeds to coutrol in the humid and sub-humid tropics of Asia, Wcst Africa, and Latin America (Garrity et al, 1997). ln Wcst Africa.…”
Section: Introductionmentioning
confidence: 99%
“…I. cylindrica is used ritually by the Balinese (Rifai & Widjaja 1979) and the Karen of northern Thailand (Potter 1997) and is employed throughout the region to thatch and adorn the roofs of bamboo huts. Alang-alang fields are decreasing throughout Indonesia; on Java the coverage has decreased from over 30% at the beginning of the 20th century to current levels of less than 2% (Garrity et al 1997); in Eastern Indonesia the increasing scarcity of alang-alang is forcing families to purchase roofing material for the first time (Potter et al 2000;J. Pfeiffer, personal observation 2006).…”
Section: Biological Invasions and Cultural Landscapesmentioning
confidence: 99%
“…cylindrica merupakan tumbuhan rumput tahunan dan dianggap sebagai gulma di lahan pertanian, tumbuh di daerah dengan curah hujan tinggi (Garrity et al 1996). Gulma tersebut umumnya tumbuh di areal tanaman tahunan.…”
Section: Komposisi Gulmaunclassified